DIPG-01. REIRRADIATION PRACTICES FOR DIFFUSE INTRINSIC PONTINE GLIOMA. (4th December 2020) - Cacciotti, Chantel; Liu, Kevin; Haas-Kogan, Daphne; Warren, Katherine
Abstract: INTRODUCTION: Diffuse intrinsic pontine gliomas (DIPG) are a leading cause of brain tumor deaths in children. Current standard of care includes focal radiation therapy (RT). Despite clinical improvement in the majority of patients, the effect is temporary and median survival is less than one year. The use of reirradiation and possible benefit has been reported in progressive DIPG, yet standardized approaches are lacking. We conducted an internet-based survey to assess physicians' practices in pediatric DIPG. METHODS: A 14-question REDCap survey regarding re-irradiation practices was emailed to 396 physicians identified through an International Pediatric Neuro-Oncology and Radiation-Oncology database. RESULTS: Response rate was 35% overall (radiation-oncologists, 28%; pediatric oncologists, 57%). Two participants were excluded (did not treat DIPG). Participants included radiation-oncologists (62%), pediatric oncologists (7%), and pediatric neuro-oncologists (29%). Most physicians (62%) treated 1–5 DIPG patients per year, with 10% treating >10/year. Reirradiation was considered a treatment option in 88%. Progressive disease or worsening clinical status were the most common reasons to consider reirradiation. The majority (84%) considered reirradiation a minimum of 6 months following initial RT. Doses varied, with median total dose 24Gy (range 12–60); 2Gy/fraction (range 1–9). Concurrent use of systemic agents with reirradiation was considered in 46%, mainly with targeted agents (37%), biologics (34%), or immunotherapy (25%). One-time reirradiation was the most common practice (71%). Interestingly, 9% of respondents would not consider reirradiation. CONCLUSION: Although, the vast majority of physicians agree with re-irradiation as a treatment option for DIPG the total doses varied, and further clinical trials are needed.